PENGARUH LIKUIDITAS DAN STRUKTUR MODAL TERHADAP PROFITABILITAS PADA INDUSTRI PULP AND PAPER YANG TERDAFTAR DI BURSA EFEK INDONESIA - Wulandari "; Ruzikna " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This study aimed to analyze and determine the effect of liquidity and capital structure on profitability. Where the independent variable in this study is the liquidity (current assets) and capital structure (debt to asset ratio) the dependent variable is an indicator of profitability with a return on assets (ROA).The sample used is secondary data devired from the financial statments of pulp and paper listed in the indonesia Stock Exchange (BEI). Samples taken by purposive sampling and sample that met the selection criteria. The samples used were as much as 7 industry. Analysis of data using multiple linear regression analysis with statistical test of hypothesis testing and statistical tests f t – assisted software SPSS 21.These results indicate that management of liquidity and capital structure simultaneously no significant effect on profitability. And partially liquidity and capital strukture also has no significant effect on profitability. This indicates that the variable X does not affect the Y either simultaneously of partially.Keywords : Liquidity, Capital Structure and Profitability